Edoxaban for stroke prevention in atrial fibrillation and age-adjusted predictors of clinical outcomes in routine clinical care - Kirchhof, Paulus; Pecen, Ladislav; Bakhai, Ameet; de Asmundis, Carlo; de Groot, Joris R; Deharo, Jean Claude; Kelly, Peter; Levy, Pierre; Lopez-de-Sa, Esteban; Monteiro, Pedro; Steffel, Jan; Waltenberger, Johannes; et al. (European heart journal. Cardiovascular pharmacotherapy, 2022)
AIMS: Patients with atrial fibrillation (AF) treated with oral anticoagulation still suffer from cardiovascular complications including cardiovascular death, stroke, and major bleeding. To identify risk factors for predicting stroke and bleeding outcomes in anticoagulated patients, we assessed 2-year outcomes in patients with AF treated with edoxaban in routine care. We also report the age-adjusted risk predictors of clinical outcomes. METHODS AND RESULTS: The Edoxaban Treatment in Routine Clinical Practice for Patients With Non-Valvular Atrial Fibrillation (ETNA-AF) Europe (NCT02944019) is a prospective, multi-centre, post-authorisation, observational study with an overall 4-year follow-up conducted in 825 centres enrolling edoxaban-treated patients in 10 European countries. Of the 13 133 patients with AF (mean age: 73.6 ± 9.5 years), 5682 (43.3%) were female. At the 2-year follow-up, 9017/13 133 patients were still on edoxaban; 1830 discontinued treatment including 937 who died (annualised event rate of all-cause death was 3.87%). 518 (2.14%) patients died of cardiovascular causes; 234 (0.97%) experienced major bleeding and 168 (0.70%) experienced stroke or systemic embolic events (SEE). Intracranial haemorrhage was noted in 49 patients (0.20%). History of transient ischaemic attack (TIA) at baseline was the strongest predictor of ischaemic stroke or SEE (Wald χ2: 73.63; P < 0.0001). Low kidney function at baseline was the strongest predictor of major bleeding (Wald χ2: 30.68; P < 0.0001). History of heart failure (HF) was the strongest predictor of all-cause (Wald χ2: 146.99; P < 0.0001) and cardiovascular death (Wald χ2: 100.38; P < 0.0001). CONCLUSION: Patients treated with edoxaban in ETNA-AF-Europe reported low 2-year event rates in unselected AF patients. Prior stroke, reduced kidney function, and HF identify patients at high risk of stroke, bleeding and all-cause/cardiovascular death, respectively.
Keywords: senioři; Embolism; Stroke; senioři nad 80 let; Brain Ischemia; Heart Failure; výsledek terapie; Middle Aged; mužské pohlaví; krvácení; Factor Xa Inhibitors; Prospective Studies; cévní mozková příhoda; Atrial fibrillation; Aged, 80 and over; Real-world; antikoagulancia; ženské pohlaví; Humans; prospektivní studie; Anticoagulants; Edoxaban; fibrilace síní; inhibitory faktoru Xa; srdeční selhání; lidé středního věku; Registry; Hemorrhage; Non-vitamin K oral anticoagulant; ischemie mozku; Female; Aged; Atrial Fibrillation; Treatment Outcome; embolie; lidé; Male